Rotations of Normal Fault Blocks Quantify Extension in the Central Tauride Intramontane Basins, SW Turkey. Issue 8 (3rd August 2018) - Koç, Ayten; van Hinsbergen, Douwe J. J.; Langereis, Cor G.
Abstract: Quantifying the amount of stretching in extensional basin systems is often challenging in the absence of seismic profiles or boreholes. However, when fault spacing and orientation as well as vertical axis rotation patterns are known, map‐view restoration may provide a good estimate of total extension. This integrated structural and paleomagnetic approach provides a relatively straightforward tool in extensional basin restoration and fault zone kinematic analysis. Here we provide results of an extensive paleomagnetic survey of the Neogene Central Tauride intramontane basins (SW Turkey), where previous work revealed a complex array of basin‐bounding normal faults and relay ramps. In total, 437 oriented cores were sampled at 43 sites distributed within Miocene‐Pliocene continental sedimentary rocks from the Ilgın, Altınapa, Yalvaç, and Beyşehir basins. Despite the more or less coherent overall strike of the mountain belt and basins, rotations vary from 42° clockwise (Yalvaç) to 10° (Beyşehir), 21° (Ilgın), and 30° (Altınapa) counterclockwise. We show that the rotation pattern is related to normal faults and lateral variations in fault displacement superimposed on regional rotation patterns. We restore these to estimate a minimum NE‐SW horizontal extension of 30–35 km across the basin system. As a consequence of our reconstruction, it appears that the Sultandağları range that exposes low‐grade metamorphic Paleozoic and Mesozoic rocks of the Geyikdağı and Bolkardağ nappes of the Taurides represents a Miocene extensional core complex. Key Points: We identify four different rotational domain in the Central Tauride intramontane basins The restoration of the rotational domains predicts a minimum NE‐SW horizontal extension of 30–35 km across the basin system The Sultandağları range may represent a Miocene extensional core complex